The use of peer tutoring with beginning readers - Nolan, Katherine (2017)
This study is an investigation into social and emotional outcomes of peer tutoring with reading, specifically student confidence, motivation and reading enjoyment. A small sample of cross age, same sex pairs from grade one and grade five were observed over a period of four weeks using the Paired Reading method. Findings suggest that participant enjoyment and motivation to read was high. Increased tutee confidence remained relatively unobservable while high levels of tutor confidence were notable. Tutor delivery, error correction and positive reinforcement were strong as a direct result of quality programme implementation in the initial stages of research. The role of the educator as facilitator and participant trainer plays a crucial part in potential social and emotional outcomes of a peer tutoring project. Data additionally revealed that ‘trio reading’ compiling one tutor with two tutees, using the same Paired Reading technique was highly engaging and enjoyable for both tutors and tutees alike. This raises further implications for future reading programmes. This research contributes to current knowledge in the field with additional qualitative findings regarding the social and emotional effects of peer tutoring.